Can Sprint Interval Training (SIT) Improve the Psychological and Physiological Health of Adolescents with SMI?. Issue 3 (3rd July 2019) - Taylor, Caitlin; Sanders, Ross; Hoon, Matthew; Starling, Jean; Cobley, Stephen
ABSTRACT: This study examined whether a structured cycle-based SIT intervention could improve psychological (symptom severity) and physiological (aerobic/anaerobic performance) health outcomes in adolescents with serious mental illness. Participants were 30 age-matched adolescents ( M = 16.00 ± 1.17 years) from Australia who completed an 8-week bicycle-based sprint interval training (SIT) program (3 days/week) or were recruited to a comparison group alongside normative care. SIT sessions consisted of 4 × 30-s maximum-effort intervals split by 4-min recovery. Primary measures examined pre–post were Positive and Negative Syndrome Scale (PANSS), World Health Organization–5 Questionnaire (WHO-5), and aerobic/anaerobic performance. Secondary outcomes were also considered (e.g., weight). Between-within analysis of variance's identified Group × Time interaction effects with moderate-to-strong effects sizes for psychological well-being (WHO-5 intervention group – M change  = + 13.06, Benjamini–Hochberg statistical procedure [BH] confirmed p = .01, n 2  = 0.24) and physiological indices (aerobic performance – est.VO2 max – intervention group – M change  = + 5.79 ml.kg −1 .min −1, BH p = .03, n 2  = 0.18; anaerobic performance – intervention group M change  = + 49.93 watts, BH p < .01, n 2  = 0.48). A significant three-way Group × Sex × Time ( p = .02, n 2  = 0.18) and Group × Time effects was apparent for Total PANSS ( M change SIT = −10.80 points, BH p = .03, n 2  = 0.17). Significant Group × Time interactions in secondary anthropometrics were also apparent (e.g., intervention group – M change weight = −0.73kg, BH p < .01, n 2  = 0.25). Findings identified that an 8-week SIT intervention improved key physiological and psychological health indices. Findings suggest that SIT can help protect and potentially improve multiple health indices in adolescents affected by serious mental illness. Abbreviations: Aerobic performance = est. VO2 max; anaerobic performance = Wingate sprint; BH = Benjamini-Hochberg statistical procedure; BW-ANOVA = Between Within - Analysis of Variance; Mchange = Mean change from pre-post intervention; PANSS = Positive and Negative Syndrome Scale; SMI = Serious Mental Illness; WHO-5 = World Health Organisation-5 Questionnaire.